2021
DOI: 10.1021/acs.analchem.1c00792
|View full text |Cite
|
Sign up to set email alerts
|

Rapid SERS Quantification of Trace Fentanyl Laced in Recreational Drugs with a Portable Raman Module

Abstract: Rapid identification and quantification of opioid drugs are of significant importance and an urgent need in drug regulation and control, considering the serious social and economic impact of the opioid epidemic in the United States. Unfortunately, techniques for accurate detection of these opioids, particularly for fentanyl, an extremely potent synthetic drug of abuse and a main perpetrator in the opioid crisis, are often not readily accessible. Therefore, a fast, highly sensitive, and preferably quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 51 publications
7
54
0
Order By: Relevance
“…It is reported that the SERS signal can improve by aggregation of nanoparticles. [21][22][23][24] Unfortunately, this process affects batch-to-batch reproducibility of SERS measurements because of the uncontrolled aggregation of nanoparticles. 25 These limitations can be circumvented by developing a nanoparticle system that can generate ultra-high SERS signal without the addition of salts for weakaffinity analyte molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the SERS signal can improve by aggregation of nanoparticles. [21][22][23][24] Unfortunately, this process affects batch-to-batch reproducibility of SERS measurements because of the uncontrolled aggregation of nanoparticles. 25 These limitations can be circumvented by developing a nanoparticle system that can generate ultra-high SERS signal without the addition of salts for weakaffinity analyte molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional methods of drug analysis such as chromatography [2], immunochromatography [3], mass spectrometry (MS) [4], nuclear magnetic resonance (NMR) [5], ultraviolet-visible spectroscopy (UV-Vis) [6], Fourier-transform infrared spectroscopy (FTIR) and IR [7], surface-enhanced Raman spectroscopy (SERS) and Raman [8], circular dichroism (CD) spectroscopy [9], and spectrofluorimetry [10], which can offer accurate and precise results, often lack portability, and can suffer from lengthy run times, high costs and complicated operation. Thus, new methods capable of providing rapid, specific responses whilst being cost effective and easy to use are still required [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that fentanyl was detected on a silver colloid at 5 ppb with a portable Raman system incorporating a 785‐nm laser. [ 20 ] A notable exception was the study using a gold sol–gel [ 28 ] that reported measuring over 150 drugs of various classes on a portable Raman system with 785‐nm laser excitation. However, the SERS reported for all these drugs (at 100 ppm in water) were summarized in a table, but only for a small number were the spectra shown.…”
Section: Introductionmentioning
confidence: 99%
“…One technology that offers great promise in overcoming such limitations is surface-enhanced Raman spectroscopy (SERS). SERS is versatile in its use and application and offers the ability to detect various drugs of concern at low concentration levels directly from surfaces, [9] as trace components in tablets or powders, [10] in wastewater, [11] and in biofluids, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] including saliva. [27][28][29][30][31][32][33][34] Additional studies have reported the SERS detection of a wide range of abused drugs in solution, [35] such as cocaine, [36] amphetamines, [37,38] ring substituted amphetamines, [39][40][41] bath salts, [42,43] opioids [21,35,[44][45][46][47][48] including drug mixtures laced with fentanyl, [49][50][51]…”
mentioning
confidence: 99%
See 1 more Smart Citation